Enzymic and permeability activity of Pseudomonas aeruginosa after treatment with sub-MICs of organic ammonium salts - Hostacká, A; Majtán, V (Folia microbiologica, 1994)
The effects of subinhibitory concentrations (1/4, 1/8, 1/16 of the MIC) of 12 organic ammonium salts of A (hard-alkyltrimethylammonium bromides) and B (soft--2-(dodecanoylamino)ethylalkyldimethylammonium bromides) homologous series on phospholipase C, proteinase, elastase and permeability activity were studied. The substances with longer substituents were more effective in reducing phospholipase C activity (hard and soft series) as well as proteinase (hard series). Phospholipase C was the most frequently and the most markedly inhibited enzyme. The organic ammonium salts were less effective in inhibiting elastase and permeability activity. Only one of the substances under study reduced all the tested activities.
Keywords: Microbial Sensitivity Tests; kapilární permeabilita; vztahy mezi strukturou a aktivitou; inhibitory proteas; Structure-Activity Relationship; pankreatická elastasa; Virulence; Type C Phospholipases; mikrobiální testy citlivosti; fosfolipasy typu C; antibakteriální látky; virulence; Capillary Permeability; Pseudomonas aeruginosa; Anti-Bacterial Agents; Pancreatic Elastase; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; Protease Inhibitors